Human mitochondrial NDUFS3 protein bearing leigh syndrome mutation is more prone to aggregation than its wild-type - Jaokar, Tulika M.; Patil, Deepak P.; Shouche, Yogesh S.; Gaikwad, Sushama M.; Suresh, C. G. (Biochimie, 2013)
NDUFS3 is an integral subunit of the Q module of the mitochondrial respiratory Complex-I. The combined mutation (T145I + R199W) in the subunit is reported to cause optic atrophy and Leigh syndrome accompanied by severe Complex-I deficiency. In the present study, we have cloned and overexpressed the human NDUFS3 subunit and its double mutant in a soluble form in Escherichia coli. The wild-type (w-t) and mutant proteins were purified to homogeneity through a serial two-step chromatographic purification procedure of anion exchange followed by size exclusion chromatography. The integrity and purity of the purified proteins was confirmed by Western blot analysis and MALDI-TOF/TOF. The conformational transitions of the purified subunits were studied through steady state as well as time resolved fluorescence and CD spectroscopy under various denaturing conditions. The mutant protein showed altered polarity around tryptophan residues, changed quenching parameters and also noticeably altered secondary and tertiary structure compared to the w-t protein. Mutant also exhibited a higher tendency than the w-t protein for aggregation which was examined using fluorescent (Thioflavin-T) and spectroscopic (Congo red) dye binding techniques. The pH stability of the w-t and mutant proteins varied at extreme acidic pH and the molten globule like structure of w-t at pH1 was absent in case of the mutant protein. Both the w-t and mutant proteins showed multi-step thermal and Gdn-HCI induced unfolding. Thus, the results provide insight into the alterations of NDUFS3 protein structure caused by the mutations, affecting the overall integrity of the protein and finally leading to disruption of Complex-I assembly. (C) 2013 Elsevier Masson SAS. All rights reserved.
Keywords: Aggregation Fluorescence lifetime; Complex-I; Leigh syndrome; NDUFS3

Highly active bile salt hydrolase from enterococcus faecalis shows positive cooperative kinetics - Chand, Deepak; Ramasamy, Sureshkumar; Suresh, C. G. (Process Biochemistry, 2016)
Bile salt hydrolase (BSH; cholylglycine hydrolase, EC 3.5.1.24) is an important enzyme that catalyses the deconjugation of bile acids conjugated with glycine or taurine and assists in the reduction of blood cholesterol levels. In the present study, we report the cloning, overexpression and characterisation of BSH gene from a gut-associated microbe Enterococcus faecalis (EfBSH). The overexpressed protein in Escherichia coli was purified to homogeneity. Optimum pH and temperature for activity were found to be 5.0 and 50 degrees C, respectively. The enzyme was considerably stable in the pH range of 5.0-7.0 and at a temperature of up to 50 degrees C. It showed high specific activity of 1390 U mg(-1) and 1289 U mg-1 for substrates such as glycocholic acid (GCA) and glycodeoxycholic acid (GDCA), respectively. The effect of additives on enzyme activity was assessed, and the detergent Triton X showed a marginally enhanced activity. The enzyme demonstrated unique enzyme kinetics of non-linear regression, thereby displaying positive cooperativity. In addition, the modulating effect of the non-substrate ligand Pen V on the hydrolysing ability of EfBSH towards bile acid such as GDCA was measured. It was observed that Pen V significantly enhanced the BSH activity. This is markedly different from the previously reported competitive inhibition of BSH activity by Pen V. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Allosteric regulation; Bile acids; Bile salt hydrolase; Enzyme kinetics; Gut organism; Penicillin V acylase